RIFM fragrance ingredient safety assessment, 1, 6-heptadien-3-one, 2-cyclohexyl-, CAS Registry Number 313973-37-4. (August 2019) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; Fryer, A.D.; et al.
Highlights: MATERIAL NAME; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.